2019
DOI: 10.1109/access.2018.2889340
|View full text |Cite
|
Sign up to set email alerts
|

Secure Transmission for Differential Quadrature Spatial Modulation With Artificial Noise

Abstract: In this paper, we investigate the secure transmission for differential quadrature spatial modulation (DQSM) with artificial noise (AN) in multiple-input single-output wiretap networks, where a cooperative jammer helps the secure transmission between transceivers in the presence of an eavesdropper. To evaluate the secrecy performance of the DQSM with AN in the considered wiretap networks, assuming Rayleigh fading, we derive exact and asymptotic closed-form expressions for secrecy outage probability and effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…It was presented that activating an extra transmit antenna to transmit AN can increase the security of SM. A similar fact was discussed in [11], where the authors proposed a secure transmission scheme for differential quadrature spatial modulation (DQSM) with AN, and it was shown that the AN technique was a meaningful idea to improve the secrecy performance. Because the AN can be also interference to the legitimate receiver, the antenna carrying AN needs to be directed to the null space, and thus, additional beamforming technique was required.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…It was presented that activating an extra transmit antenna to transmit AN can increase the security of SM. A similar fact was discussed in [11], where the authors proposed a secure transmission scheme for differential quadrature spatial modulation (DQSM) with AN, and it was shown that the AN technique was a meaningful idea to improve the secrecy performance. Because the AN can be also interference to the legitimate receiver, the antenna carrying AN needs to be directed to the null space, and thus, additional beamforming technique was required.…”
Section: Introductionmentioning
confidence: 56%
“…The received signal at the legitimate receiver Bob, y b , can be rearranged as follows by inserting the result in (11) into (9).…”
Section: Secrecy Rate Analysismentioning
confidence: 99%
“…What's more, each data block actually transmitted depends on the actual data currently and the previously data block, so as to achieve differential modulation in the network using the DSM scheme, thereby eliminating the need for CSI during demodulation by the receiver [19]. Considering the benefits of DSM, authors combine DSM with PLS and investigate the secure transmission based on differential quadrature spatial modulation with artificial noise in MISO wiretap networks in [22]. Despite the above benefits, the PLS by the DSM scheme in MIMO CRNs has not been investigated so far.…”
Section: A Backgroundmentioning
confidence: 99%
“…Theorem 2: By using DSM-MRC scheme we can calculate the secrecy outage probability of P DSM −M RC out (R s ), which is get as (22), shown at the bottom of next page.…”
Section: A Tas-mrc Schemementioning
confidence: 99%
“…On the basis of SOP, the ST more comprehensively measures the reliability and security of the system in a whole way, which is the product of the complementary probability of P out (R S ) and the predetermined secrecy rate R S (Equation 24, [43]), [44]. Thus, the throughput expression of the two schemes can be written as T…”
Section: Secrecy Throughputmentioning
confidence: 99%